2013
DOI: 10.1155/2013/876973
|View full text |Cite
|
Sign up to set email alerts
|

Large-Eddy Simulation of the Aerodynamic and Aeroacoustic Performance of a Ventilation Fan

Abstract: There are controversial requirements involved in developing numerical methodologies in order to compute the flow in industrial fans. The full resolution of turbulence spectrum in such high-Reynolds number flow configurations entails unreasonably expensive computational costs. The authors applied the study to a large unidirectional axial flow fan unit for tunnel ventilation to operate in the forward direction under ambient conditions. This delivered cooling air to the tunnel under routine operation, or hot gase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…18 They used the open source code OpenFOAM, a code previously validated by researchers studying the flow-field in both aerospace and industrial turbomachinery applications. 19–26…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 They used the open source code OpenFOAM, a code previously validated by researchers studying the flow-field in both aerospace and industrial turbomachinery applications. 19–26…”
Section: Introductionmentioning
confidence: 99%
“…18 They used the open source code OpenFOAM, a code previously validated by researchers studying the flow-field in both aerospace and industrial turbomachinery applications. [19][20][21][22][23][24][25][26] In this paper, the authors first describe the tunnel ventilation fan that is the subject of the reported research and consider the tunnel ventilation system applications into which they have installed it. They then define the pressure pulses to which they have subjected the fan and clarify the computational approach that occurs with their modelling.…”
Section: Introductionmentioning
confidence: 99%